1996
DOI: 10.1785/bssa0860051507
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency analysis of seismic background noise as a function of wind speed and shallow depth

Abstract: We used a deep (1500 m) cased borehole near the town of Datil in west-central New Mexico to study high-frequency (>1 Hz) seismic noise characteristics. The remote site had very low levels of cultural noise, but strong winds (winter and spring) made the site an excellent candidate to study the effects of wind noise on seismograms. Along with a three-component set of surface sensors (Teledyne Geotech GS-13), a vertical borehole seismometer (GS-28) was deployed at a variety of depths (5, 43, and 85 m) to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(33 citation statements)
references
References 14 publications
2
30
0
1
Order By: Relevance
“…Wind can be the most intrusive sound on a recording and, if the wind is constantly louder than the river, blowing out the microphone, then it is not possible to extract a river component. In a remote location away from cultural noise sources, wind has also been recorded on seismic monitors at the surface, contaminating the recorded signal at speeds of only 6.5 mph (Withers et al., 1996). Ronan et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wind can be the most intrusive sound on a recording and, if the wind is constantly louder than the river, blowing out the microphone, then it is not possible to extract a river component. In a remote location away from cultural noise sources, wind has also been recorded on seismic monitors at the surface, contaminating the recorded signal at speeds of only 6.5 mph (Withers et al., 1996). Ronan et al.…”
Section: Methodsmentioning
confidence: 99%
“…Wind can be the most intrusive sound on a recording and, if the wind is constantly louder than the river, blowing out the microphone, then it is not possible to extract a river component. In a remote location away from cultural noise sources, wind has also been recorded on seismic monitors at the surface, contaminating the recorded signal at speeds of only 6.5 mph (Withers et al, 1996). Ronan et al (2017) found wind to be the most probable source of high power, low spectral coherence noise on infrasound recordings, while Anthony et al (2018) suggested that without wind filters, and if deployed close to a river, infrasound acoustic signals were likely unsuitable for smaller river systems.…”
Section: Sound Analysismentioning
confidence: 99%
“…Ambient seismic noise is broadly divided into two categories, microseisms (infra low frequency waves) (Longuet-Higgins 1950 ; Oliver and Ewing 1957 ; Stutzmann et al 2000 ) and earth’s hum (infra gravity waves) (Rhie and Romanowicz 2004 ; Nishida et al 2007 ; Webb 2007 ). Cultural noise, wind and infrasound pressure variations together are generally the dominant source of noise in the frequency band 1–20 Hz (e.g., Withers et al 1996 ; Le Pichon 2004 ; McNamara and Buland 2004 ; Marzorati and Bindi 2006 ; Burtin et al . 2008 ) which is also the band where most of microearthquakes at local and regional distance appear.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity of seismic measurements to wind has been extensively studied. References [11,12] demonstrated the coherent signature of wind induced seismic noise, while references [13,14] reported low coherency of this type of seismic noise though with limited and sparse spatial measurements. By comparing wind speed and direction from two anemometers, [14] showed that wind is incoherent on the 100 m length scale.…”
Section: Introductionmentioning
confidence: 99%
“…The turbulent interaction of wind with surface objects that results in the more challenging low coherent wind induced seismic noise is the subject of this paper. We use higher sensor density than [13,14] and measure coherence lengths to analyze the coherency of wind induced seismic noise. We use the ability to resolve background coherent seismic noise to highlight the effect.…”
Section: Introductionmentioning
confidence: 99%